'Little boy blue' - Awre, Gabrielle (The University of Hull, 2017)
Gabrielle added this lullaby to the project as it had always been very effective getting babies to sleep in her family. The tune is different from the one heard on many of the lullaby websites. Gabrielle learnt it from her mother who was from Cardiff and she learnt it from her father whose family was Irish, so this could be an Irish tune.